A Dual GLP-1/GIP Receptor Agonist Is More Effective than Liraglutide in the A53T Mouse Model of Parkinson’s Disease - Zijuan Zhang; Ming Shi; Zhengmin Li; Yuan Ling; Luke Zhai; Ye Yuan; He Ma; Li Hao; Zhonghua Li; Zhenqiang Zhang; Christian Hölscher (Parkinson's Disease)
Parkinson’s disease (PD) is a complex syndrome with many elements, such as chronic inflammation, oxidative stress, mitochondrial dysfunction, loss of dopaminergic neurons, build-up of alpha-synuclein (α-syn) in cells, and energy depletion in neurons, that drive the disease. We and others have shown that treatment with mimetics of the growth factor glucagon-like peptide 1 (GLP-1) can normalize energy utilization, neuronal survival, and dopamine levels and reduce inflammation. Liraglutide is a GLP-1 analogue that recently showed protective effects in phase 2 clinical trials in PD patients and in Alzheimer disease patients. We have developed a novel dual GLP-1/GIP receptor agonist that can cross the blood-brain barrier and showed good protective effects in animal models of PD. Here, we test liraglutide against the dual GLP-1/GIP agonist DA5-CH (KP405) in the A53T tg mouse model of PD which expresses a human-mutated gene of α-synuclein. Drug treatment reduced impairments in three different motor tests, reduced levels of α-syn in the substantia nigra, reduced the inflammation response and proinflammatory cytokine levels in the substantia nigra and striatum, and normalized biomarker levels of autophagy and mitochondrial activities in A53T mice. DA5-CH was superior in almost all parameters measured and therefore may be a better drug treatment for PD than liraglutide.